SHORT FOOD SUPPLY CHAINS – BENEFITS FOR CONSUMERS AND FOOD PRODUCERS - Agnieszka Kawecka (Journal of Agribusiness and Rural Development, 2015)
In the age of globalization of food markets, short supply chains are the reversion to traditional food distribution systems. A large group of consumers is willing to reach for local food, frequently also buyers of organic food delivered directly from food producers. The paper presents the characteristics of short food supply chains, food distribution system is shown by: markets, direct purchases from producers and modern forms of providing consumers with local products. Qualitative study was conducted among organic food markets participants – exhibitors (food producers), and visitors (customers). Consumers notice many benefi ts from buying and consuming local food, among others, higher quality of products, favorable price-quality performance ratio, and assurance of purchased products origin. Producers for the most important fi nd greater share in the total price of products and receiving feedback information from consumers. Short supply chains are also resulting signifi cant environmental benefi ts eg. limited transport. A new approach to the subject of local foods and the benefi ts of shortening the supply chain is refl ected in the policy of the European Union – including through programs on rural development.